Multilocus Sequence Typing Reveals Extensive Genetic Diversity of the Emerging Fungal Pathogen Scedosporium aurantiacum - Harun, Azian; Kan, Alex; Schwabenbauer, Katharina; Gilgado, Felix; Perdomo, Haybrig; Firacative, Carolina; Losert, Heidemarie; Abdullah, Sarimah; Giraud, Sandrine; Kaltseis, Josef; Fraser, Mark; Buzina, Walter; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Scedosporium spp. are the second most prevalent filamentous fungi after Aspergillus spp. recovered from cystic fibrosis (CF) patients in various regions of the world. Although invasive infection is uncommon prior to lung transplantation, fungal colonization may be a risk factor for invasive disease with attendant high mortality post-transplantation. Abundant in the environment, Scedosporium aurantiacum has emerged as an important fungal pathogen in a range of clinical settings. To investigate the population genetic structure of S. aurantiacum, a MultiLocus Sequence Typing (MLST) scheme was developed, screening 24 genetic loci for polymorphisms on a tester strain set. The six most polymorphic loci were selected to form the S. aurantiacum MLST scheme: actin (ACT), calmodulin (CAL), elongation factor-1α (EF1α), RNA polymerase subunit II (RPB2), manganese superoxide dismutase (SOD2), and β-tubulin (TUB). Among 188 global clinical, veterinary, and environmental strains, 5 to 18 variable sites per locus were revealed, resulting in 8 to 23 alleles per locus. MLST analysis observed a markedly high genetic diversity, reflected by 159 unique sequence types. Network analysis revealed a separation between Australian and non-Australian strains. Phylogenetic analysis showed two major clusters, indicating correlation with geographic origin. Linkage disequilibrium analysis revealed evidence of recombination. There was no clustering according to the source of the strains: clinical, veterinary, or environmental. The high diversity, especially amongst the Australian strains, suggests that S. aurantiacum may have originated within the Australian continent and was subsequently dispersed to other regions, as shown by the close phylogenetic relationships between some of the Australian sequence types and those found in other parts of the world. The MLST data are accessible at http://mlst.mycologylab.org. This is a joined publication of the ISHAM/ECMM working groups on “Scedosporium/Pseudallescheria Infections” and “Fungal Respiratory Infections in Cystic Fibrosis”.